Biokinetic Parameter Values of Denitrification Process of Fishery Industrial Wastewater on Differentiated COD/TKN Ratios - Bustami Ibrahim; Anna C. Erungan; . Heriyanto (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2009)
Indonesian Fishery Industries has been developed very rapidly. This can cause negative effect such as increase in wastewater that involved highly organic substrates that will danger the environment. This effluent must be treated before flowed it to environment and usually treated by biological wastewater treatment through nitrification and denitrification process simultaneously using activated sludge. This study conducted denitrification process using activated sludge with treatment using different COD/TKN ratios which are 2.44, 2.96, and 3.26 and monitored in Hydraulic Retention Time (HRT) 4.5, 3.5, 2.5, 2.0, 1.5, 1.0, 0.75, 0.5 and 0.25 day. Result showed that for determining the biokinetic parameters such as Ks, Kno (Monod Constant saturated), Y (yield), kd (endogenous decay) also μm result for range of COD/TKN ratios 2.44–3.26 are 3.04 are 14.93–17.26 mg/lCOD, 1.21-1.60 mg/l NO3, 0.171-0.193 mg VSS/mg COD, 0.014-0.062 day-1 and 1.64–0.97 day-1. These biokinetic parameters can be used to improve the wastewater treatment plant.Keywords: activated sludge, biokinetic parameter, denitrification